Gene Discovery Using Twins. (April 2020) - Duffy, David; Sturm, Rick; Zhu, Gu; MacGregor, Stuart
Abstract: One of Nick's key early achievements at QIMR was to establish a twin study on melanoma risk factors. The Brisbane Twin Nevus Study (BTNS) had an initial focus on nevus (mole) count in adolescents but, reflecting Nick's broad interests, expanded in scope enormously over the decades. In the skin cancer arena, BTNS was essential to genetic discoveries in melanoma, eye color and pigmentation. Later studies amassed data on thousands of phenotypes, ranging from molecular phenotypes such as gene expression to studies where gene mapping findings in adolescents turned out to have translational potential in late-onset diseases. Nick's twin data have formed the basis for an enormous range of discoveries, with Nick and his colleagues continuing to capitalize on these data.